(untitled) (Diametros, 2011)
The goal of this article is to formulate a conception of the entrepreneur based on the branches of social theory that are related to the material circumstances of life in society: property, poverty, wealth, work and action. The article outlines the impact of Thorstein Veblen’s and Werner Sombart’s thought on the modern theory of the enterprise. Author advances the thesis that independence making a living constitutes the beginning of the enterprise, which is the foundation of modern capitalism. The modern capitalist enterprise frees itself from its founder, and thus cannot be limited by him.